2013
DOI: 10.1177/1049909113509400
|View full text |Cite
|
Sign up to set email alerts
|

Biofield Therapies for Symptom Management in Palliative and End-of-Life Care

Abstract: Terminally ill patients experience negative symptoms at end of life (EOL) that hinder well-being and quality of life (QOL). Current intervention strategies are not always effective or feasible. A focused literature review to evaluate the use of biofield therapies (ie, Therapeutic Touch, Healing Touch, and Reiki) to manage the symptoms in EOL revealed no studies on the use these therapies, specifically in this population. Evidence from studies on relevant populations (patients with cancer, elderly patients, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 46 publications
0
15
0
2
Order By: Relevance
“… 46 In addition, there is need for investigation of biofield therapies in palliative care, where these therapies are often delivered. 47 …”
Section: Other Clinical Conditions Warranting Further Studymentioning
confidence: 99%
See 1 more Smart Citation
“… 46 In addition, there is need for investigation of biofield therapies in palliative care, where these therapies are often delivered. 47 …”
Section: Other Clinical Conditions Warranting Further Studymentioning
confidence: 99%
“…46 In addition, there is need for investigation of biofield therapies in palliative care, where these therapies are often delivered. 47 Several reviews since the 2010 best evidence synthesis of Jain and Mills have examined clinical research based on the biofield modality. 14,15,19 Overall, these reviews point to the same general conclusions: there is promising but limited evidence based on relatively few studies with insufficient sample sizes as well as methodological issues that could be improved to better understand the effects of biofield therapies in a clinical context.…”
Section: Other Clinical Conditions Warranting Further Studymentioning
confidence: 99%
“…7, 8, 9, 10, 11 Our findings suggest that CAM therapies are often employed as appropriate adjuncts with pharmaceuticals. 14, 15, 16, 17, 13, 18, 19 In addition, CAM therapies may promote comfort and wholeness for both the infant and the family at end of life. 7, 8, 9, 10, 11 As additional complementary and alternative therapies gain acceptance in the medical community, further data will be need to examine the use of these therapies in perinatal hospice and palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…7, 8, 10, 11 These therapies consist of a group of non-pharmacological, non-invasive, holistic interventions that are usually provided by members of the interdisciplinary team or by trained volunteers. 12, 6 The most common CAM therapies available by hospices are massage, acupuncture, music therapy, guided imagery, energy healing, aromatherapy, and pet therapy, 7, 8, 9, 10, 11, 13 with the goals of relieving pain and anxiety 14, 15, 16, 17, 13, 18, 19 and promoting comfort and wholeness. 7, 8, 9, 10, 11 …”
mentioning
confidence: 99%
“…[ 157 159 163 164 165 ] Pedro et al .,[ 166 ] concluded that there is some evidence to support the efficacy of ET for reducing pain and fatigue and promoting relaxation in cancer patients. Furthermore, a review of 30 studies by Henneghan and Schnyer[ 167 ] supported the use of ET for reducing pain and stress, and enhancing QOL in patients needing PC at end-of-life. Similar positive effect of therapeutic touch on symptom management in cancer patients has been reported by Tabatabaee et al .,[ 168 ] in their review of six studies.…”
Section: Ommon C Omplementary mentioning
confidence: 99%